2001
DOI: 10.1007/s002130100910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the cannabinoid receptor antagonist SR 141716, alone and in combination with dexfenfluramine or naloxone, on food intake in rats

Abstract: These data show that SR 141716 is an effective anorectic agent using both palatable foods and bland chow, and is selective because water intake was unaffected. SR 141716 is also effective orally and has an effect sustained for at least several days. There appears to be a synergistic interaction between opioid and cannabinoid systems in the regulation of feeding, whereas the combination of a serotonin releasing agent and the CB1 antagonist is additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 15 publications
10
69
1
4
Order By: Relevance
“…Whereas sibutramine, for example, advanced the BSS, thus indicating a satiating effect [355], the combination of sibutramine and the opioid antagonist naloxone showed rather infra-additive effects [355]. Combining fenfluramine with rimonabant had additive effects on food intake [356], whereas the combination of mCPP and naltrexone did not provide any support for a clinically useful combination [81]. In conclusion, these findings show that each potential combination requires individual testing.…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
“…Whereas sibutramine, for example, advanced the BSS, thus indicating a satiating effect [355], the combination of sibutramine and the opioid antagonist naloxone showed rather infra-additive effects [355]. Combining fenfluramine with rimonabant had additive effects on food intake [356], whereas the combination of mCPP and naltrexone did not provide any support for a clinically useful combination [81]. In conclusion, these findings show that each potential combination requires individual testing.…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
“…72,73 In addition, food intake studies showed that rimonabant inhibited the intake of both regular chow or palatable food. 24,74,75 Tetrahydrocannabinol (THC) has also been shown to stimulate the intake of either chow or highfat sweetened diet. 76 These data generally support a model in which CB1R inverse agonists reduce the intake of all macronutrients with no selectivity related to palatability.…”
Section: Do Cb1r Agents Produce Weight Loss-independent Effects?mentioning
confidence: 99%
“…For example, a 1 mm 3 'hedonic hotspot' was recently found in the medial shell where m opioid receptor activation by DAMGO microinjections tripled positive 'liking' orofacial reactions that are elicited by sucrose taste in rats (Peciña and Berridge, 2005), and stimulated food intake (though the intake 'wanting' site extended further) (Bakshi and Kelley, 1993;Zhang and Kelley, 2000;Peciña and Berridge, 2005). Opioid and endocannabinoid neurotransmissions are known to positively interact (Tanda et al, 1997;Kirkham and Williams, 2001;Navarro et al, 2001;Rowland et al, 2001;Williams and Kirkham, 2002b;Verty et al, 2003;Solinas and Goldberg, 2005;Vigano et al, 2005;Caille and Parsons, 2006;Cota et al, 2006), raising the possibility that endocannabinoid receptor activation might increase 'liking' for natural rewards in the same hedonic hotspot of the medial accumbens shell where opioids do so.…”
Section: Introductionmentioning
confidence: 99%